The conceptions of memory in the Information Science in Brazil: preliminary study on the occurrence of the subject in scientific production. - Oliveira, Eliane Braga; Rodrigues, Georgete Medleg (PontodeAcesso, 2009)
It shows partial results of descriptive and explicative research about conceptions of memory identified in the literature specialized in Information Science and its consequences on the studies of the information scientists in Brazil. It is considered that the subject memory plays peripheral role in the concerns of the area. It presents a quantitative analysis of the data obtained from the documents identification that approaches the subject memory: dissertations and theses produced in brazilian programs of Information Science and articles of journals entailed to these programs. The partial results do not evidence a direct concern from the researchers with the subject memory. It can be observed at the small numbers of dissertations, theses and periodic articles about memory.